Immunoglobulin free light chains: an inflammatory biomarker of diabetes - Matsumori, Akira; Shimada, Toshio; Shimada, Miho; Drayson, Mark T. (Inflammation Research, 2020)
Objective Inflammation is increasingly understood as playing an important role in type 2 diabetes mellitus (T2D) development. A critical mechanism of the inflammatory cascade in developing T2D is nuclear factor-kappa B (NF-kB) activation. As immunoglobulin free light chains (FLC) could be a biomarker of activation of NF-kB, we measured FLC in patients with T2D. Subjects The age range of the 77 patients with T2D and the 75 healthy control participants were 45–87 years (median 60) and 25–72 years (median 51), respectively. Methods Serum FLC kappa and lambda were assayed by a competitive-inhibition multiplex Luminex assay. Results The concentration of circulating FLC the kappa/lambda ratio was lower in patients with T2D than in healthy volunteers. The area under the receiver operating curve (ROC-AUC) of the FLC kappa/lambda ratio showed the largest ROC-AUC compared with other FLC variables and hemoglobin A1c (HbA1c). The diagnostic performance for distinguishing between T2D and healthy control was a sensitivity of 0.96 and a specificity of 1. The odds ratio was 0.000018. Conclusions These results suggest that FLC kappa/lambda may be more specific and sensitive for the diagnosis of T2D than HbA1c, and thus represents a potentially promising biomarker of inflammation.